Analisis Biaya Satuan (Unit Cost) dengan Metode Activity Based Costing (ABC) di Poliklinik Jantung RSU dr. H. Koesnadi Bondowoso - Sumiati, Sumiati; Witcahyo, Eri; Ramani, Andrei (Jurnal Ekonomi Kesehatan Indonesia, 2019)
Determination of rate calculated based on unit cost, based on Bondowoso Regent Regulation Number 62 of 2017, RSU dr. H. Koesnadi Bondowoso unit cost calculates using the Double Distribution method. Double Distribution (DD) method is not appropriate to be applied because it does not reflect activity, method based on activity, precise and accurate so that it can provide the right information is Activity Based Costing (ABC) method. RSU Dr. H. Koesnadi Bondowoso has not made unit cost calculation using Activity Based Costing (ABC) method, especially for outpatient installation. The purpose of this research is unit cost analysis with Activity Based Costing method in the heart polyclinic of RSU Dr. H. Koesnadi Bondowoso. The research method based on Activity Based Costing (ABC) calculation method. The unit of analysis was heart poyclinic at RSU Dr. H. Koesnadi Bondowoso. Unit cost calculated with Activity Based Costing (ABC) method. Based on the calculation result with 2017 data a unit cost obtained, electrocardiogram is Rp. 47,689, echocardiography Rp. 113,212 and treadmill is Rp. 221,547. The conclusion shown that the unit cost is lower than the specified rate.